Cryptocurrency Regulation in Indonesia: Regulation Review and Potential Risks from A Cyber Law Perspective - Fahira, Siti Hapsah; Daimah, Daimah; Mu'amar, Irkham (Politeknik Siber Cerdika Internasional, 2024)
Cryptocurrency has grown rapidly in Indonesia and attracted the attention of various parties, both from economic and legal aspects. However, cryptocurrency regulation in Indonesia is still in its early stages with dual regulations between Bank Indonesia which prohibits its use as a means of payment, and Bappebti which recognizes cryptocurrency as a tradable commodity. This background creates legal uncertainty and cyber risks that need to be addressed seriously. This study aims to analyze the legal framework governing cryptocurrency in Indonesia, as well as identify potential risks arising from a cyber law perspective. This study uses a juridical-normative approach with a descriptive-analytical method, focusing on literature studies related to cryptocurrency regulations, laws and regulations, and industry reports. The results of the study show that cryptocurrency regulations in Indonesia are still limited to aspects of commodity trading without fully considering the threatening cyber risks, such as fraud and money laundering. In addition, comparisons with countries such as Japan and Singapore show that Indonesia needs to strengthen the existing legal framework to reduce the risk of cybercrime. More comprehensive regulatory reforms are needed to address existing legal loopholes, protect consumers, and create a safe cryptocurrency ecosystem.